Carbon monoxide impairs mitochondria‐dependent endosomal maturation and antigen presentation in dendritic cells. Issue 12 (23rd October 2015) - Riquelme, Sebastián A.; Pogu, Julien; Anegon, Ignacio; Bueno, Susan M.; Kalergis, Alexis M.
Abstract : Heme‐oxygenase 1 (HO‐1) prevents T cell‐mediated inflammatory disease by producing carbon monoxide (CO) and impairing DC immunogenicity. However, the cellular mechanisms causing this inhibition are unknown. Here, we show that CO impairs mitochondrial function in DCs by reducing both the mitochondrial membrane potential and ATP production, and resembling the effect of a nonlethal dose of a classical mitochondria uncoupler carbonyl cyanide m‐chlorophenyl hydrazone (CCCP). Moreover, both CO and CCCP reduced cargo transport, endosome‐to‐lysosome fusion, and antigen processing, dampening the production of peptide‐MHC complexes on the surface of DCs. As a result, the inhibition of naive CD4 + T‐cell priming was observed. Furthermore, mitochondrial dysfunction in DCs also significantly reduced CD8 + T cell‐dependent type 1 diabetes onset in vivo. These results showed for the first time that CO interferes with T‐cell priming by blocking an unknown mitochondria‐dependent antigen‐processing pathway in mature DC. Interestingly, other immune functions in DCs such as antigen capture, cytokine secretion, costimulation, and cell survival relied on glycolysis, suggesting that oxidative phosphorylation might only play a key role for the maturation of antigen‐containing endosomes. In conclusion, CO produced by HO‐1 impairs antigen‐dependent inflammation by regulating DC immunogenicity by a mitochondria‐dependent mechanism.